The effect of hamstring donor-site block for functional outcomes and rehabilitation after anterior cruciate ligament reconstruction - Cai, Zijun; Yang, Yuntao; Liu, Di; Lu, Wenhao; Pan, Linyuan; He, Miao; Xie, Wenqing; Yu, Dengjie; Li, Hengzhen; Jin, Hongfu; Li, Yusheng; Xiao, Wenfeng (Frontiers in Surgery, 2023)
Purpose: To determine the effect of local infiltration anesthesia (LIA) at the donor site combined with a femoral nerve block (FNB) on short-term postoperative pain and the functional outcomes and rehabilitation after arthroscopic hamstring tendon autograft anterior cruciate ligament reconstruction (ACLR). Methods: This study was a single center, randomized controlled trial. Seventy-three subjects with ACL rupture were enrolled. Participants were randomly allocated to two groups, 47 in the experimental group (Group A) and 26 in the control group (Group B). All operations were performed under FNB. In Group A, 10 ml of 1% ropivacaine was injected precisely at the hamstring donor site. Patients in Group B were treated with the same amount of saline. Preoperatively and for 48 hours postoperatively, pain scores based on the numerical rating scale (NRS) and consumption of opioids were recorded. In addition, knee functions were assessed by the International Knee Documentation Committee Subjective Knee Form (IKDC), the Lysholm score, and the Knee injury and Osteoarthritis Outcome Score (KOOS) preoperatively and postoperatively at 1 and 3 months. In addition, we applied the KNEELAX3 arthrometer to evaluate the stability of the knee preoperatively and postoperatively so that subjective and objective knee conditions were obtained to help us assess knee recovery in a comprehensive manner. Results: The hamstring donor-site block reduced pain within the first 24 postoperative hours. There were no significant differences between two groups in pain intensity preoperatively and beyond 24 hours postoperatively. Furthermore, there were no differences between the groups concerning knee functions preoperatively or in the short-term follow-up at 1 and 3 months. Conclusion: LIA at the donor site can effectively improve the early postoperative pain of patients after ACLR and reduce the use of opioids without affecting the functional outcomes of the surgery.